From capital to equality: evaluating how foreign direct investment and domestic direct investment influence the gini ratio in Bandung Regency (2011–2024) - Simamora, Daniel (Institute of Computer Science (IOCS), 2025)
Income inequality remains a persistent challenge in developing countries, including Indonesia, particularly amid the significant inflow of capital through investment. As one of Indonesia’s regencies, Bandung Regency is no exception to this issue. This study aims to analyze the effect of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI), as variables representing investment, on income inequality as measured by the Gini Ratio in Bandung Regency. Using annual time-series data from 2011 to 2024, this study applies a multiple linear regression model with the Ordinary Least Squares (OLS) method to estimate the impact of these two types of investment. The econometric analysis reveals divergent results. FDI is found to have a positive and statistically significant effect on the Gini Ratio, indicating that an increase in foreign investment tends to widen income inequality. Conversely, DDI shows a negative, but not statistically significant, effect on inequality. This finding implies that the characteristics and structural linkages of investment with the local economy, rather than merely the volume of incoming capital, are crucial determinants of distributional outcomes. The primary policy implication for the local government is the need to transition from a strategy focused solely on the quantity of investment realization to a qualitative approach that prioritizes and incentivizes investments particularly DDI that have stronger leverage in creating local economic linkages and promoting equity